A Critical Perspective on the Conceptualization of Risk in Behavioral and Experimental Finance - Felix Holzmeister; Christoph Huber; Stefan Palan (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
Risk is one of the key aspects in financial decision-making and therefore an integral part of the behavioral economics and finance literature. Focusing on the conceptualization of the term "risk", which researchers have addressed from numerous angles, this comment aims to offer a critical perspective on the interactions between risk preferences (a latent trait), risk perceptions (how individuals judge whether something is risky), and risk-taking behavior as distinct concepts, and hence to guide future research on (individual-level) decision-making processes in this direction.
Keywords: D81; D91; G41; 330; risk-taking behavior; risk preferences; risk perception